Diffusive Spreading in Nature, Technology and Society (Springer International Publishing, 2018)
This book deals with randomly moving objects and their spreading. The objects considered are particles like atoms and molecules, just as living beings like humans, animals, plants, bacteria and even abstract entities like ideas, rumors, information, innovations and linguistic features. The book explores and communicates the laws behind these movements and reports about astonishing similarities and very specific features typical of the given object under considerations. Leading scientists in disciplines as different as archeology, epidemics, linguistics and sociology, in contact with their colleagues from engineering, natural sciences and mathematics, introduce into the phenomena of spreading as relevant for their fields. An introductory chapter on "Spreading Fundamentals" provides a common basis for all these considerations, with a minimum of mathematics, selected and presented for enjoying rather than frustrating the reader.